A reassessment of transport mechanisms of some rock avalanches in the Mackenzie Mountains, Yukon and Northwest Territories, Canada - Kaiser, P. K.; Simmons, J. V. (Canadian Geotechnical Journal, 1990)
The transport mechanism of some rock avalanches of the Mackenzie Mountains in the Yukon and Northwest Territories of Canada is reassessed on the basis of evidence collected during fieldwork and by comparison with results from numerical simulations of the debris flow mechanism. A new hypothesis of glaciation-related transport is advanced as an alternate explanation of apparently very mobile rock avalanches with anomalous travel distances. By the example of the Avalanche Lake slide, it is demonstrated that the debris was most likely not deposited on the current topography but on valley glacier ice at an elevation of about 400–500 m above the valley bottom. This conclusion is supported by field evidence, an empirical runup relationship, and the results from numerical flow simulations. A qualitative interpretation of other debris deposits suggests that several events in the Mackenzie Mountains can be interpreted in the same manner. Key words: rock avalanches, rock slides, debris transport, debris flow modelling, Mackenzie Mountains, Northwest Territories.